(untitled) (Ágora Journal, 2020)
The Porto Revolution started in 1820 brought critical consequences to the fate of the Luso-Brazilian Empire. Shaken by liberal ideas, the Old Portuguese Regime lost space to constitutionalism. In the wake of the constitution, press freedom made it possible to create several periodicals in the Empire, contributing to the circulation of ideas and news. Attentive to this context, this article analyzes the Pernambuco press between the years 1821 and 1824, seeking to understand the political discussions and how these newspapers and this province were inserted in the problems of the Empire.